2000
DOI: 10.1034/j.1600-0684.2000.290310.x
|View full text |Cite
|
Sign up to set email alerts
|

SIVcpz from a naturally infected Cameroonian chimpanzee: Biological and genetic comparison with HIV‐1 N

Abstract: Thus far, simian immunodeficiency virus from chimpanzees (SIVcpz) genomes have been characterized as Pan troglodytes troglodytes and show a strong relation with human immunodeficiency virus (HIV)-1 N in their env genes. We fully characterized another SIVcpz from P. t. troglodytes. This chimpanzee (Cam5) was, as was also the host of SIVcpz-cam3, wild born in Cameroon, a region where all three groups of HIV-1 (M, N and O) co-occur. In contrast to other SIVcpz, SIVcpz-cam5 was isolated immediately after the rescu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 29 publications
4
16
0
Order By: Relevance
“…Figure 3 shows that SIVcpz strains from chimpanzees in Tanzania and the Democratic Republic of Congo, all of whom were identified as P. t. schweinfurthii by mtDNA analyses, are most closely related to SIVcpzANT (75,93). Conversely, three newly identified Cameroonian viruses group most closely with other SIVcpzPtt strains, and their hosts were typed as P. t. troglodytes (10,17,50). Interestingly, one SIVcpz-infected ape (CAM4) was classified as a P. t. vellerosus, but on further investigation it was found that CAM4 had been housed with CAM3 and that their viruses were virtually identical (17).…”
Section: The Origin Of Hiv-1mentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3 shows that SIVcpz strains from chimpanzees in Tanzania and the Democratic Republic of Congo, all of whom were identified as P. t. schweinfurthii by mtDNA analyses, are most closely related to SIVcpzANT (75,93). Conversely, three newly identified Cameroonian viruses group most closely with other SIVcpzPtt strains, and their hosts were typed as P. t. troglodytes (10,17,50). Interestingly, one SIVcpz-infected ape (CAM4) was classified as a P. t. vellerosus, but on further investigation it was found that CAM4 had been housed with CAM3 and that their viruses were virtually identical (17).…”
Section: The Origin Of Hiv-1mentioning
confidence: 99%
“…Additional surveys of both wild-caught and wild-living chimpanzee populations, however, began to identify new SIVcpz strains, suggesting that natural infection is not as rare as originally thought. Four SIVcpz strains (CAM3, CAM4, CAM5, and CAM13) were obtained from orphaned chimpanzees in Cameroon (17,50,51), while additional cases of SIVcpz infection were documented in wild-living chimpanzee communities in Tanzania (TAN1 to TAN5) and the Kisangani area of the Democratic Republic of Congo (72,73,75,93). Moreover, the existence of two separate clades of SIVcpz, infecting members of the central (SIVcpzPtt) and eastern chimpanzee (SIVcpzPts) subspecies, was confirmed.…”
Section: The Origin Of Hiv-1mentioning
confidence: 99%
“…In order to determine whether this deletion in exon III is present or not in other African nonhuman primates, we examined genomic DNA of 13 animals from five distinct species: patas monkey (Erythrocebus patas), l'Hoest monkey (Cercopithecus lhoesti), white-collared mangabey (Cercocebus torquatus lunulatus), gray-cheeked mangabey (Cercocebus albigena), and chimpanzee (Pan troglodytes troglodytes) (33). The latter corresponds to a naturally SIVcpz-infected chimpanzee (Cam5) (34). We observed again a smaller amplicon, indicating the same deletion in all of the animals studied (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Patas monkeys (Erythrocebus patas) were held in captivity at the Pasteur Institute in Bangui. L'Hoest's monkeys (Cercopithecus lhoesti lhoesti), white-collared mangabeys (Cercocebus torquatus lunulatus), gray-cheeked mangabeys (Cercocebus albigena), and a naturally SIVcpz-infected chimpanzee (Pan troglodytes, Cam5) were housed in European and Cameroonian zoos (33,34). Rhesus (Macaca mulatta) and cynomolgus (M. fascicularis) macaques were housed at the primate center of CEA, Fontenay aux Roses, France.…”
Section: Methodsmentioning
confidence: 99%
“…The HIV-1 N YBF30 and YBF116 (3,74) nef alleles were also amplified from PBMC. The SIVcpz US (20) (14) and Cam5 (14,48) with human PBMC. The remaining SIVcpz nef alleles were amplified from plasma RNA derived from Noah (ch-No) and an uncultured PBMC sample derived from Niko (ch-Ni), respectively.…”
Section: Methodsmentioning
confidence: 99%